2018
DOI: 10.1161/circoutcomes.118.004710
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities Among Adult Recipients of Bystander Cardiopulmonary Resuscitation in the Public

Abstract: Background: Bystander cardiopulmonary resuscitation (BCPR) improves survival from out-of-hospital cardiac arrest (OHCA), yet BCPR rates remain low. It is unknown whether BCPR delivery disparities exist based on victim gender. We measured BCPR rates by gender in private and public environments, hypothesizing that females would be less likely than males to receive BCPR in public settings, with an associated difference in survival to hospital discharge. Methods and Results: We analyzed data from adult, non-trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
134
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 44 publications
5
134
3
4
Order By: Relevance
“…Many studies have confirmed that women are less likely to receive bystander CPR even when OHCA occurs in the presence of witnesses [21]. In the study by Blewer et al [22] of 19.331 OHCA cases, when the incident occurred in a public place, 39% of women and 45% of men received help-higher than the results obtained in the present study (28 and 53%, respectively).…”
Section: Discussioncontrasting
confidence: 66%
“…Many studies have confirmed that women are less likely to receive bystander CPR even when OHCA occurs in the presence of witnesses [21]. In the study by Blewer et al [22] of 19.331 OHCA cases, when the incident occurred in a public place, 39% of women and 45% of men received help-higher than the results obtained in the present study (28 and 53%, respectively).…”
Section: Discussioncontrasting
confidence: 66%
“…Similar gender disparities in bystander CPR have also been observed in the general population. 23 Overall, further study on the challenges and dilemmas that dialysis clinic personnel face in managing cardiac arrest is needed to guide the development of programs and interventions to improve CPR use in dialysis clinics.…”
Section: Discussionmentioning
confidence: 99%
“…With this understanding of vulnerability in mind, it is clear that women have long been susceptible to harm in the context of medical practice and research . In clinical practice, men are more likely to receive comprehensive investigation and treatment, including for hypercholesterolaemia, ischaemic heart disease, heart failure, cardiorespiratory arrest, atrial fibrillation, rheumatoid arthritis, end‐stage renal disease and dementia . Women are also more likely to have their illness disregarded and their pain pathologised, or ignored .…”
Section: Introductionmentioning
confidence: 99%